Arabinoxylan hydrolyzates as immunomodulators in Caco-2 and HT-29 colon cancer cell lines. Issue 1 (14th December 2016) - Mendis, Mihiri; Leclerc, Estelle; Simsek, Senay
Abstract : Structure-function relationship of wheat derived arabinoxylan hydrolyzates as immunomodulators was investigated using intestinal cell lines. Fine structural details had a strong correlation with the immunological properties of the wheat arabinoxylan hydrolyzates. Abstract : The use of plant derived polysaccharides as health promoters has gained immense interest in the past few years. Arabinoxylan (AX) is the predominant non-starch polysaccharide in cereals and grasses including wheat. The current research aimed to investigate the structure–function relationship of arabinoxylan hydrolyzates (AXH), obtained by the enzymatic hydrolysis of AX using xylanase and arabinofuranosidase as immunomodulators in two colon cancer cell lines: Caco-2 and HT-29. Fine structural details had a strong correlation with the immunological properties of the wheat AXH. As a general trend, as the presence of arabinose substitution increased in the AXH, the production of proinflammatory cytokines, IL-8 and TNF-α, decreased in both cell lines. Thus, AXH with a higher degree of arabinose substitution might be better adept in lowering inflammation in colon cancer cells.